Investigating Psychiatric Disorders in Patients with Suicide Attempt - Zoha Sadeghian; Parvane Rashidpour; Hamidreza Ghasemirad; Seyed Mojtaba Yassini Ardekani; Shahab ali Shirkhoda; Golraste Kholasezade; Hamid Owliaey; Reza Bidaki (Journal of Social Behavior and Community Health, 2024)
Background: Attempting suicide is considered one of the important indicators of the mental health of individuals in society. One of the important issues in suicide is psychiatric disorders and related factors. Given that no comprehensive study was conducted in Yazd province, this study aimed to assess psychiatric disorders in patients with suicide attempts. Methods: This analytical cross-sectional study was conducted on 344 patients with suicide attempts at Shahid Beheshti Hospital from March 2021 to March 2022. The type of psychiatric illness was diagnosed based on the clinical interview and DSM-5 diagnostic criteria. All information was extracted from medical records entered into SPSS version 22 and analyzed. P < 0.05 was assumed significant. Results: The average age of the patients was 27.09 ± 11.78 years. Among them, 145 were men (42.2%) and 199 were women (57.8%). The most common psychiatric disorder was Major depressive disorder (MDD) (46.5%). Moreover, the lowest frequency of psychiatric disorders was schizophrenia (1.2%). There was a significant relation between psychiatric disorders and variables, including age, number of suicides, gender, and suicide method (P < 0.05). A significant relation was seen between the severity of diseases and gender (P < 0.05). Conclusion: Among the various types of psychiatric disorders, MDD was more prevalent in individuals who commit suicide. Hence, it was essential to focus more attention on this particular group of patients. Additionally, the use of medication was the most common method of suicide. It should also be noted that the severity of suicide was higher in men.